Catalyst component recycled based on waste Z-N catalyst and used for ethylene polymerization or copolymerization as well as preparation method and application of catalyst component
By grinding the waste Z-N catalyst and reacting with titanium compounds and organoaluminum compounds, high-activity and low fine powder content are obtained, which solves the waste catalyst resources and environmental protection problems, and achieves its efficient reuse in ethylene polymerization or copolymerization.
Patent Information
- Application Number
- CN202311135763.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art is difficult to effectively recycle and reuse waste Z-N catalysts, resulting in waste of resources and environmental protection problems.
By grinding the waste Z-N catalyst, dissolved in a titanium compound, reacting with the organoaluminum compound, and after precipitation, filtering, washing and drying, the catalyst component with high activity, high bulk density and low fine powder content was finally obtained.
It realizes efficient recycling and reuse of waste Z-N catalysts, has good environmental value and economic benefits, and is suitable for ethylene polymerization or copolymerization.
Smart Images

Figure CN119569915A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst component for polyolefins, in particular to a catalyst component for ethylene polymerization or copolymerization recovered based on a waste ZN catalyst, a preparation method and application in catalyzing ethylene polymerization or copolymerization. Background Art
[0002] Polyolefin catalysis technology is the core of the rapid development of the polyolefin industry. The global polyolefin catalyst market is expected to reach US$1.87 billion in 2021, maintaining an annual growth rate of 5.2%. Among them, Ziegler-Natta (ZN) catalysts will dominate the polyolefin catalyst market both now and in the future.
[0003] However, in the process of synthesizing ZN catalysts, batches of substandard quality are inevitably produced, mainly including low catalyst polymerization activity, low polymerization bulk density, a lot of fine powder, and particle size that does not meet the requirements (too large or too small); during the screening process of the catalyst, a certain amount of oversize material will be generated due to particle agglomeration. These catalysts that do not meet the requirements need to be treated as waste harmlessly before they can meet the discharge standards.
[0004] The main component of discarded ZN catalyst is magnesium chloride, and it also contains titanium, electron donors, volatile components and other components. The current general treatment methods are mostly environmentally friendly treatment methods such as hydrolysis, neutralization, sedimentation, solid-liquid separation, etc. However, the treatment process will also produce a large amount of wastewater, waste gas, waste solid and low-value waste, which not only increases the factory's operating expenses, but also causes a waste of resources.
[0005] If the discarded ZN catalyst can be reused to prepare ethylene polymerization or copolymerization catalyst, this will undoubtedly provide a new solution. Summary of the invention
[0006] The purpose of the present invention is to provide a catalyst component for ethylene polymerization or copolymerization based on waste ZN catalyst, which is recovered and used for ethylene polymerization or copolymerization. The catalyst component not only has the characteristics of high activity, high bulk density and low fine powder content when used for ethylene polymerization or copolymerization, but also has good environmental value and economic benefits.
[0007] Another object of the present invention is to provide a method for preparing the catalyst component.
[0008] Another object of the present invention is to provide use of the catalyst component in catalyzing ethylene polymerization or copolymerization.
[0009] In the synthesis of ethylene polymerization or copolymerization catalyst components, the present invention first grinds the discarded ZN catalyst, then dissolves it in a titanium compound, and then reacts with an organic aluminum compound, washes, dries, etc., so that a catalyst with excellent comprehensive performance can be finally obtained. The prepared catalyst is used for ethylene polymerization or copolymerization, has the characteristics of high activity, high bulk density, low fine powder content, and has good environmental value and economic benefits.
[0010] In order to achieve the object of the present invention, the catalyst component for ethylene polymerization or copolymerization based on waste ZN catalyst recovery of the present invention is obtained by comprising the following reaction steps:
[0011] 1) Firstly, the waste ZN catalyst is ground under nitrogen protection;
[0012] 2) dissolving at least one ground waste ZN catalyst in a titanium compound and adding an inert solvent for dilution;
[0013] 3) Then react with at least one organic aluminum compound to precipitate a solid containing magnesium and titanium, which is then sedimented, filtered, washed and dried to obtain the product.
[0014] Wherein, the waste ZN catalyst in step 1) refers to the unqualified material produced in the preparation process of ZN catalyst. Its main components include chlorine, magnesium, titanium, electron donor, organic volatiles, etc. The waste ZN catalyst can be ground alone, or it can be mixed with at least one magnesium halide, alkoxy magnesium halide, alkoxy magnesium, alkyl magnesium, alkyl magnesium halide, alkyl alkoxy magnesium in any proportion; preferably, the waste ZN catalyst and magnesium halide are mixed in any proportion; most preferably, the mixing ratio of the waste ZN catalyst and magnesium halide is 1:0.1-10. Its dosage is calculated based on 1 mole of the magnesium compound contained.
[0015] The magnesium halide is magnesium chloride, magnesium bromide, magnesium iodide or magnesium chloride, preferably magnesium chloride.
[0016] The alkoxy magnesium halide is methoxymagnesium chloride, ethoxymagnesium chloride, propoxymagnesium chloride, n-butoxymagnesium chloride, isobutoxymagnesium chloride, methoxymagnesium bromide, ethoxymagnesium bromide, propoxymagnesium bromide, n-butoxymagnesium bromide, isobutoxymagnesium bromide, methoxymagnesium iodide, ethoxymagnesium iodide, propoxymagnesium iodide, n-butoxymagnesium iodide, isobutoxymagnesium iodide, among which methoxymagnesium chloride, ethoxymagnesium chloride and isobutoxymagnesium chloride are preferred.
[0017] The alkoxy magnesium is methoxy magnesium, ethoxy magnesium, propoxy magnesium, isopropoxy magnesium, butoxy magnesium, isobutoxy magnesium, methoxyethoxy magnesium, methoxypropoxy magnesium, ethoxypropoxy magnesium, ethoxyisopropoxy magnesium, ethoxybutoxy magnesium, ethoxyisobutoxy magnesium; preferably ethoxy magnesium and isobutoxy magnesium.
[0018] The alkyl magnesium is methyl magnesium, ethyl magnesium, propyl magnesium, n-butyl magnesium, isobutyl magnesium, n-butyl octyl magnesium, etc., among which ethyl magnesium and n-butyl magnesium are preferred.
[0019] The alkyl magnesium halide is methyl magnesium chloride, ethyl magnesium chloride, propyl magnesium chloride, n-butyl magnesium chloride, isobutyl magnesium chloride, methyl magnesium bromide, ethyl magnesium bromide, propyl magnesium bromide, n-butyl magnesium bromide, isobutyl magnesium bromide, methyl magnesium iodide, ethyl magnesium iodide, propyl magnesium iodide, n-butyl magnesium iodide, isobutyl magnesium iodide, among which methyl magnesium chloride, ethyl magnesium chloride and isobutyl magnesium chloride are preferred.
[0020] The alkyl alkoxy magnesium is methyl methoxy magnesium, methyl ethoxy magnesium, methyl propoxy magnesium, methyl n-butoxy magnesium, methyl isobutoxy magnesium, ethyl methoxy magnesium, ethyl ethoxy magnesium, ethyl propoxy magnesium, ethyl n-butoxy magnesium, ethyl isobutoxy magnesium, propyl methoxy magnesium, propyl ethoxy magnesium, propyl propoxy magnesium, propyl n-butoxy magnesium, propyl isobutoxy magnesium, n-butyl methoxy magnesium, n-butyl ethoxy magnesium, n-butyl propoxy magnesium, n-butyl n-butoxy magnesium, n-butyl isobutoxy magnesium, isobutyl methoxy magnesium, isobutyl ethoxy magnesium, isobutyl propoxy magnesium, isobutyl n-butoxy magnesium, isobutyl isobutoxy magnesium, among which butyl ethoxy magnesium is preferred.
[0021] In step 1), the grinding time is 0.1 to 100 h, preferably 1 to 75 h, and most preferably 1 to 50 h; the grinding temperature is 0 to 100 ° C, preferably 10 to 75 ° C, and most preferably 10 to 50 ° C; the average particle size of the particles after grinding is 0.1 to 200 μm, preferably 0.1 to 30 μm, and most preferably 0.1 to 15 μm.
[0022] In step 2), the general formula of the titanium compound is TiX 2 n (OR 3 ) 4-n , where R 3 is an aliphatic hydrocarbon group or an aromatic hydrocarbon group having 1 to 14 carbon atoms, X 2is halogen, and n is 0, 1, 2, 3 or 4. Preferably, the titanium compound comprises titanium halide, alkyl titanium halide and alkoxy titanium, wherein titanium halide is such as titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, alkyl titanium halide is such as methoxy titanium trichloride, ethoxy titanium trichloride, propoxy titanium trichloride, n-butoxy titanium trichloride, dimethoxy titanium dichloride, diethoxy titanium dichloride, dipropoxy titanium dichloride, di-n-butoxy titanium dichloride, trimethoxy titanium chloride, triethoxy titanium chloride, tripropoxy titanium chloride, tri-n-butoxy titanium chloride, alkoxy titanium is such as tetraethoxy titanium, tetrapropoxy titanium, tetrabutoxy titanium. These titanium compounds can be used in combination of one or more. Among them, alkoxy titanium is preferably used. More preferably, tetraethoxy titanium, tetrabutoxy titanium and a mixture of any proportion thereof are used.
[0023] Among them, the titanium compound is 0.05 to 50 moles, preferably 0.1 to 20 moles, preferably 0.1 to 10 moles, and most preferably 0.1 to 5 moles per mole of magnesium compound in the recovered waste ZN catalyst.
[0024] In order to make the dissolution more complete, an inert diluent is added after the magnesium compound and the titanium compound are mixed. The inert diluent can be an aromatic compound, an alkane compound or a mixture of any proportion thereof which is liquid at room temperature. The aromatic compound is benzene, toluene, xylene, ethylbenzene, propylbenzene, trimethylbenzene, chlorobenzene, dichlorobenzene, etc. The alkane compound is hexane, heptane or cyclohexane. Aromatics and alkanes can be used alone or in combination.
[0025] In step 3), the amount of the organoaluminum compound is 0.2 to 100 moles, preferably 0.2 to 20 moles, and most preferably 0.2 to 10 moles, per mole of the magnesium compound in the recovered waste ZN catalyst.
[0026] The general formula of the organoaluminum compound is AlR 4 m X 3 3-m , where R 4 is hydrogen, a hydrocarbon group having 1 to 20 carbon atoms, X 3 is a halogen, and m is 0≤m≤3. These compounds include, the organic aluminum compound is selected from at least one alkyl aluminum, alkyl aluminum halide; the alkyl aluminum compound is such as triethyl aluminum, tributyl aluminum, triisobutyl aluminum, tri-n-hexylaluminum or tri-n-octylaluminum; the alkyl aluminum halide is diethyl aluminum monochloride, monoethyl aluminum dichloride, sesquiethyl aluminum, diisobutyl aluminum dichloride, diisopropyl aluminum monochloride or methyl n-propyl aluminum monochloride; the organic aluminum compound is preferably a combination of alkyl aluminum and alkyl aluminum chloride in any proportion.
[0027] Most preferably, the amount of alkyl aluminum is 0.01 to 2 moles and the amount of alkyl aluminum halide is 0.2 to 10 moles per mole of magnesium compound in the recovered waste ZN catalyst.
[0028] Another object of the present invention is to provide a method for preparing the catalyst component.
[0029] 1) Firstly, the waste ZN catalyst is ground under nitrogen protection;
[0030] 2) dissolving at least one ground waste ZN catalyst in a titanium compound and adding an inert solvent for dilution;
[0031] 3) Then react with at least one organic aluminum compound to precipitate a solid containing magnesium and titanium, which is then sedimented, filtered, washed and dried to obtain the product.
[0032] The recovered waste ZN catalyst, titanium compound, inert diluent, organic aluminum compound, etc. in the preparation method of the catalyst component have the same scope and structure as the aforementioned content.
[0033] The grinding time in step 1) of the preparation method of the catalyst component is 0.1 to 100 hours, preferably 1 to 75 hours, and most preferably 1 to 50 hours; the grinding temperature is 0 to 100°C, preferably 10 to 75°C, and most preferably 10 to 50°C; the effect of grinding is to form uniform small particles of the waste catalyst, and the average particle size of the particles after grinding at the grinding temperature is 0.1 to 200 μm, preferably 0.1 to 30 μm, and most preferably 0.1 to 15 μm.
[0034] The reaction temperature in step 2) of the preparation method of the catalyst component is arbitrary, preferably 50-200°C; the added inert diluent is preferably not higher than the boiling point of the selected inert diluent. The dissolution time is also arbitrary, so that the titanium compound and the ground waste recovery catalyst completely form a homogeneous solution.
[0035] The organic aluminum compound in step 3) of the preparation method of the catalyst component can be added as a pure substance or as a dilute solution with an inert diluent, preferably as a solution to be added dropwise to reduce the reaction rate during the addition. The reaction temperature can be selected to be no higher than the boiling point of the inert solvent contained in the homogeneous solution and the organic aluminum compound in step 3), preferably 20 to 80°C. The time of addition is arbitrary, preferably not more than 10 hours. After the addition is completed, the reaction temperature can be appropriately increased to make the reaction more complete, and the reaction temperature is preferably not more than the boiling point of the inert solvent in the system, preferably 20 to 80°C. The time of addition is arbitrary, preferably not more than 10 hours.
[0036] The processes of sedimentation, filtration, washing, etc. can be selectively repeated multiple times to remove free chemical substances. The temperature of the above operation is arbitrary, and preferably does not exceed the boiling point of the inert solvent used.
[0037] The time of the above operation is arbitrary. The solid component finally separated is dried in vacuum or blown with nitrogen to obtain the catalyst component.
[0038] The catalyst component of the present invention and an organic aluminum compound can form a catalyst for ethylene polymerization or copolymerization.
[0039] Organoaluminum compounds have been widely recognized and used as components of olefin catalysts. Their general formula is AlR 5 y X 4 3-y , where R 5 is hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, X 4 is halogen, and y is 1, 2 or 3.
[0040] The organoaluminum compound includes trialkylaluminum compounds, alkylaluminum halides and mixtures thereof in any proportion, preferably triethylaluminum, triisobutylaluminum, diethylaluminum monochloride, ethylaluminum dichloride, and more preferably triethylaluminum and triisobutylaluminum.
[0041] The optional ethylene comonomer is an olefin having the general formula CH2=CHR6, wherein R6 is C1-C 12 Alkyl groups such as straight-chain olefins: propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene; branched-chain olefins such as 3-methyl-1-butene and 4-methyl-1-pentene; and dienes such as butadiene, vinylcyclopentene and vinylcyclohexene. These olefins may be used alone or in combination.
[0042] The catalyst component of the present invention can be used in currently known ethylene polymerization and / or copolymerization processes, including kettle slurry process, loop slurry process, gas phase fluidized bed process, and the polymerization conditions can be selected from the conditions commonly used in the art. Therefore, the polymerization is generally carried out at 30 to 180° C., preferably 50 to 120° C. In any polymerization process used, the catalyst component can be pre-contacted with an alkyl aluminum compound before being introduced into a polymerization reactor. The pre-contact step can be carried out in the absence of a polymerizable olefin.
[0043] The present invention provides a catalyst component for ethylene polymerization or copolymerization recovered from waste ZN catalyst as raw material, a preparation method and application thereof. The catalyst component for ethylene polymerization not only has the characteristics of high activity, high bulk density, uniform particle size distribution and low fine powder content, but also has good environmental value and economic benefits.
[0044] Among the existing methods for treating waste ZN catalysts, the most common method is to hydrolyze the ZN catalyst and neutralize it with sodium hydroxide, and finally obtain a large amount of low-value products such as inorganic salts and titanium dioxide. In the process of treatment, a large amount of waste liquid, waste gas and waste solid will be generated, which increases the operating expenses of the factory and also causes a waste of resources.
[0045] In the waste ZN catalyst, magnesium chloride, titanium compound and electron donor (or possibly none) are in a stable physical and chemical state. When recycling the ZN catalyst, the present invention destroys both its physical structure and its chemical structure, and removes the electron donor as much as possible.
[0046] The inventors have found through repeated experiments that the physical structure of the waste ZN catalyst is destroyed by grinding. By changing the grinding conditions, the particle size of the waste ZN catalyst after grinding can be controlled, and the magnesium chloride crystals in the waste ZN catalyst after grinding are arranged randomly and disorderly; after being dissolved in the titanium compound, the physical structure of the waste ZN catalyst is completely and thoroughly destroyed.
[0047] Destroying the chemical structure of the waste ZN catalyst and removing the electron donor is achieved by adding an organic aluminum compound.
[0048] After adding the organoaluminum compound, the titanium compound is Ti 4+ Reduction to Ti 3+ and Ti 2+ At the same time, the organoaluminum compound plays the role of a halogenating agent, reacting with the alkoxy in the solution, completely destroying the chemical bond between magnesium chloride, titanium compound and electron donor, and forming a new catalyst with magnesium chloride as a carrier and a large number of active sites; the organoaluminum compound undergoes a reduction reaction with the electron donor in the waste ZN catalyst (taking the waste ZN catalyst ① as an example), first reducing dibutyl phthalate to butanol and dimethylol, and then continuing to react with the organoaluminum compound to generate an alkoxyaluminum compound, which is washed with saturated alkanes for many times and finally removes the electron donor compound. The catalyst component thus obtained is used for ethylene polymerization or copolymerization, and not only has the characteristics of high activity, high bulk density, and low fine powder content, but also has good environmental value and economic benefits.
[0049] The reaction formula of organoaluminum compound and dibutyl phthalate is as follows:
[0050] BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 This is a SEM image of the recovered waste ZN catalyst component ① of the present invention;
[0052] Figure 2This is a SEM image of the recovered waste ZN catalyst component ② of the present invention;
[0053] Figure 3 This is a SEM image of the recovered waste ZN catalyst component ③ of the present invention;
[0054] Figure 4 This is a SEM image of the recovered waste ZN catalyst component ④ of the present invention. DETAILED DESCRIPTION
[0055] The present invention is further described below with examples, which is conducive to a better understanding of the present invention and its advantages and effects, but the examples are only used to illustrate the present invention rather than to limit the present invention.
[0056] Characterization
[0057] Composition of the catalyst The metal elements in the catalyst were determined by spectrophotometry, the halogen was determined by silver nitrate titration, and the alkoxy was determined by gas chromatography.
[0058] Particle size distribution of polymer
[0059] ASTM E1187
[0060] Melt index measurement
[0061] ASTM D1238
[0062] Bulk density of polymer
[0063] DIN 53194
[0064] The operations for preparing the catalyst components in this example were all carried out in an air-tight state.
[0065] The content and particle size distribution of the components ① to ④ of the recycled waste ZN catalyst used in the embodiment are shown in Table 1, and the SEM is shown in Table Figure 1-4 .
[0066] Table 1 Component content and particle size of recycled waste ZN catalyst
[0067]
[0068] Example 1
[0069] 1. Preparation of catalyst components:
[0070] Take 50g of the recycled waste ZN catalyst① and grind it in a grinding kettle for 16h under nitrogen protection. The temperature in the grinding kettle is 30℃. After grinding, the mixture is placed in a sealed container under nitrogen protection. The particle size after grinding is 13.4μm.
[0071] In a 500ml 5-necked flask with stirring and fully replaced with nitrogen, add 4g of the ground recycled waste catalyst ① and 23.8g of tetrabutoxytitanium, then heat to 110℃ and keep constant for 3 hours, cool to 20℃, add 100ml of n-hexane treated with dehydration and deoxygenation, stir for 10min; add 100ml of 2mol / L monochlorodiethylaluminum hexane solution dropwise within 2h, stir for 30min, then add 10ml of 2mol / L tri-n-hexylaluminum hexane solution dropwise, heat to 60℃ at a uniform speed after dripping, solids gradually precipitate during the heating process, filter, wash 4 times with 100ml of hexane, and vacuum dry to obtain 21.3g of solids. The catalyst composition is shown in Table 2.
[0072] 2. Aggregation
[0073] After nitrogen was fully replaced in a 2L stainless steel reactor, 1L of n-hexane was added, 5ml of 0.5mol / L triethylaluminum hexane solution and 80mg of catalyst hexane solution were added, the temperature was raised to 70°C, hydrogen was introduced to make the pressure in the reactor reach 0.28MPa, and ethylene was introduced to make the total pressure in the reactor reach 0.73MPa, and polymerization was carried out at 80°C for 2 hours. After the reaction was completed, the reactor was cooled and stirring was stopped to discharge the reaction product. The polymerization results are shown in Table 3.
[0074] Example 2
[0075] 1. Preparation of catalyst components: Same as Example 1, except that the grinding time was changed to 32 hours. The particle size after grinding was tested to be 9.7 μm. The catalyst composition is shown in Table 2.
[0076] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0077] Example 3
[0078] 1. Preparation of catalyst components: Same as Example 1, except that the waste ZN catalyst ① is recovered by the waste ZN catalyst ②. The catalyst composition is shown in Table 2.
[0079] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0080] Example 4
[0081] 1. Preparation of catalyst components: Same as Example 1, except that the waste ZN catalyst ① is recycled instead of the waste ZN catalyst ③. The catalyst composition is shown in Table 2.
[0082] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0083] Example 5
[0084] 1. Preparation of catalyst components: Same as Example 1, except that the waste ZN catalyst ① is recycled instead of the waste ZN catalyst ④, and the tri-n-hexylaluminum hexane solution is no longer added. The catalyst composition is shown in Table 2.
[0085] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0086] Example 6
[0087] 1. Preparation of catalyst components: Same as Example 1, except that the grinding time was changed to 48 h. The particle size after grinding was tested to be 7.2 μm. The catalyst composition is shown in Table 2.
[0088] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0089] Example 7
[0090] 1. Preparation of catalyst components: Same as Example 1, except that the recovered waste catalyst ① is changed to 50% ① and 50% ②, and the grinding temperature is changed to 40° C. The catalyst composition is shown in Table 2.
[0091] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0092] Example 8
[0093] 1. Preparation of catalyst components: Same as Example 2. Catalyst composition is shown in Table 2.
[0094] 2. Aggregation:
[0095] After nitrogen is fully replaced in a 2L stainless steel reactor, 1L of n-hexane is added, 5ml of 0.5mol / L triethylaluminum hexane solution and 80mg of catalyst hexane solution are added, the temperature is raised to 70°C, hydrogen is introduced to make the pressure in the reactor reach 0.48MPa, and ethylene is introduced to make the total pressure in the reactor reach 0.73MPa, and polymerization is carried out at 80°C for 2 hours. After the reaction is completed, the reactor is cooled and stirring is stopped to discharge the reaction product. The polymerization results are shown in Table 3.
[0096] Example 9
[0097] 1. Preparation of catalyst components: Same as Example 7. Catalyst composition is shown in Table 2.
[0098] 2. Polymerization: Same as in Example 8. See Table 3 for the polymerization results.
[0099] Example 10
[0100] 1. Preparation of catalyst components: Same as Example 1. The only difference is that 25 g of recycled waste ZN catalyst ① and 25 g of anhydrous magnesium chloride are mixed and ground under nitrogen protection. The particle size after grinding is 8.6 μm. The catalyst composition is shown in Table 2.
[0101] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0102] Embodiment 11
[0103] 1. Preparation of catalyst components: Same as Example 10. Catalyst composition is shown in Table 2.
[0104] 2. Polymerization: Same as Example 8. The polymerization results are shown in Table 3.
[0105] Example 12
[0106] 1. Preparation of catalyst components: Same as Example 1, except that tri-n-hexylaluminum hexane solution is not added. The catalyst composition is shown in Table 2.
[0107] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0108] Example 13
[0109] 1. Preparation of catalyst components: Same as Example 12. Catalyst composition is shown in Table 2.
[0110] 2. Polymerization: Same as Example 8. The polymerization results are shown in Table 3.
[0111] Embodiment 14
[0112] 1. Preparation of catalyst components: Same as Example 4, except that tri-n-hexylaluminum hexane solution is not added. The catalyst composition is shown in Table 2.
[0113] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0114] Embodiment 15
[0115] 1. Preparation of catalyst components: Same as Example 14. Catalyst composition is shown in Table 2.
[0116] 2. Polymerization: Same as Example 8. The polymerization results are shown in Table 3.
[0117] Comparative Example 1
[0118] 1. Preparation of catalyst components:
[0119] In a 500ml 5-necked flask with nitrogen fully replaced and stirred, add 4g of diethoxymagnesium and 23.8g of tetrabutoxytitanium (Ti / Mg=2), then heat to 110℃ and keep constant for 3 hours, cool to 50℃, add 100ml of n-hexane treated with dehydration and deoxygenation, and stir for 10min; add 100ml of 2mol / L monochlorodiethylaluminum hexane solution dropwise within 2h, and heat to 60℃ at a uniform rate after dripping. Solids gradually precipitate during the heating process, filter, and wash twice with 100ml of hexane to obtain a solid precipitate. After filtering, wash four times with 60ml of hexane. After vacuum drying, 15g of solid is obtained. The catalyst composition is shown in Table 2. The polymerization method is the same as in Example 1, and the polymerization results are shown in Table 3.
[0120] Comparative Example 2
[0121] 1. Preparation of catalyst components: Recover discarded ZN catalyst④ without grinding.
[0122] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0123] Comparative Example 3
[0124] 1. Preparation of catalyst components: same as Comparative Example 1.
[0125] 2. Polymerization: Same as Example 8. The polymerization results are shown in Table 3.
[0126] Table 2 Catalyst composition and particle size distribution
[0127]
[0128] It can be seen from Tables 2 and 3 that the solid catalyst component prepared by the present invention has the characteristics of high activity, high bulk density, uniform particle size distribution and low fine powder content.
[0129] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
[0130] The terms used herein are only for illustration of specific embodiments and are not intended to limit the present invention. Unless otherwise defined, all terms (including technical terms and scientific terms) used herein are the same as those understood by those of ordinary skill in the art to which the present invention belongs. It should also be made clear that, except for clear definitions herein, terms such as those generally defined in dictionaries should be interpreted as having a consistent meaning in the context of this specification and the related art, and should not be interpreted as idealized or overly formalized.
[0131]
Claims
1. A catalyst component for ethylene polymerization or copolymerization based on waste ZN catalyst recovery, characterized in that: The preparation process includes the following steps: 1) Firstly, the waste ZN catalyst is ground under nitrogen protection; 2) dissolving at least one ground waste ZN catalyst in a titanium compound and adding an inert solvent for dilution; 3) Then react with at least one organic aluminum compound to precipitate a solid containing magnesium and titanium, which is then sedimented, filtered, washed and dried to obtain the product.
2. The catalyst component for ethylene polymerization or copolymerization according to claim 1, characterized in that The amount of each reactant is calculated based on the amount of magnesium compound in the recovered waste ZN catalyst. The titanium compound is 0.05 to 50 moles, preferably 0.1 to 20 moles, preferably 0.1 to 10 moles, and most preferably 0.1 to 5 moles; the organoaluminum compound is 0.2 to 100 moles, preferably 0.2 to 20 moles, and most preferably 0.2 to 10 moles.
3. The catalyst component for ethylene polymerization or copolymerization according to claim 1 or 2, characterized in that: The waste ZN catalyst is ground alone, or mixed with at least one selected from magnesium halide, alkoxy magnesium halide, alkoxy magnesium, alkyl magnesium, alkyl magnesium halide, alkyl alkoxy magnesium in any proportion and then ground; preferably, the waste ZN catalyst and magnesium halide are mixed in any proportion; most preferably, the mixing ratio of the waste ZN catalyst and magnesium halide is 1:0.1 to 10.
4. The catalyst component for ethylene polymerization or copolymerization according to any one of claims 1 to 3, characterized in that: In step 1), the grinding time of the waste ZN catalyst is 0.1 to 100 h, preferably 1 to 75 h, and most preferably 1 to 50 h; the grinding temperature is 0 to 100° C., preferably 10 to 75° C., and most preferably 10 to 50° C.; the average particle size of the particles after grinding is 0.1 to 200 μm, preferably 0.1 to 30 μm, and most preferably 0.1 to 15 μm.
5. The catalyst component for ethylene polymerization or copolymerization according to any one of claims 1 to 4, characterized in that: The general formula of the titanium compound is TiX 1 n (OR 1 ) 4-n , where R 1 is an aliphatic group or an aromatic hydrocarbon group having 1 to 14 carbon atoms, X 1 is halogen, and n is 0, 1, 2, 3, or 4.
6. The catalyst component for ethylene polymerization or copolymerization according to claim 5, characterized in that The titanium compound includes titanium halides, alkoxy titanium halides and alkoxy titanium, wherein the titanium halides are titanium tetrachloride, titanium tetrabromide or titanium tetraiodide, the alkoxy titanium halides are methoxy titanium trichloride, ethoxy titanium trichloride, propoxy titanium trichloride, n-butoxy titanium trichloride, dimethoxy titanium dichloride, diethoxy titanium dichloride, dipropoxy titanium dichloride, di-n-butoxy titanium dichloride, trimethoxy titanium chloride, triethoxy titanium chloride, tripropoxy titanium chloride, tripropoxy titanium chloride or tri-n-butoxy titanium chloride, and the alkoxy titanium is tetraethoxy titanium, tetrapropoxy titanium and tetrabutoxy titanium; the titanium compound preferably uses alkoxy titanium; more preferably tetraethoxy titanium, tetrabutoxy titanium and a combination thereof in any proportion.
7. The catalyst component for ethylene polymerization or copolymerization according to any one of claims 1 to 6, characterized in that: The general formula of the organoaluminum compound is AlR 2 m X 2 3-m , where R 2 is hydrogen, a hydrocarbon group having 1 to 20 carbon atoms; X 2 is a halogen, and m is 0≤m≤3.
8. The catalyst component for ethylene polymerization or copolymerization according to claim 7, characterized in that The organoaluminum compound is selected from at least one alkylaluminum and (or) alkylaluminum halide; the alkylaluminum compound is triethylaluminum, tributylaluminum, triisobutylaluminum, tri-n-hexylaluminum or tri-n-octylaluminum; the alkylaluminum halide is diethylaluminum monochloride, monoethylaluminum dichloride, sesquiethylaluminum, diisobutylaluminum dichloride, diisopropylaluminum monochloride or methyl-n-propylaluminum monochloride; the organoaluminum compound is preferably a combination of alkylaluminum and alkylaluminum chloride in any proportion.
9. The method for preparing a catalyst component for ethylene polymerization or copolymerization according to any one of claims 1 to 8, characterized in that: It includes the following steps: 1) Firstly, the waste ZN catalyst is ground under nitrogen protection; 2) dissolving at least one ground waste ZN catalyst in a titanium compound and adding an inert solvent for dilution; 3) Then react with at least one organic aluminum compound to precipitate a solid containing magnesium and titanium, which is then sedimented, filtered, washed and dried to obtain the product.
10. A catalyst for olefin polymerization, characterized in that: Comprising the following components or the reaction products of the following components: a) a catalyst solid component according to any one of claims 1 to 8; b) and a general formula of AlR 3 y X 3 3-y An organoaluminum compound, wherein R 3 is hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, X 3 is halogen, and y is 1, 2 or 3.